Perjamuan Tuhan di Korintus - Vries, Richardo Martin Emmanuel De (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
Paul in his first letter to the church at Corinthians condemned the church at Corinth. The criticism was made because the assembly there considered the Lord's banquet which they often held was a banquet in general, it was not separated from the banquets in public places. That supper is no longer remembered as the Lord's act on the last night with His Disciples. Paul concerning this phenomenon. In addition, the banquet at Corinth did not bring fellowship to the church, instead it brought division to the church. In this article, the author will discuss some of the main problems above contained in the text of 1 Corinthians, and draw on the theological meaning contained in the text.